Zadacha Kuznecov Predely 10-16

Материал из PlusPi
Перейти к: навигация, поиск

Условие задачи

Вычислить предел функции:

<math>\lim_{x\to -2} \frac{\sqrt[3]{x-6}+2}{x+2}</math>

Решение

<math>\lim_{x\to -2} \frac{\sqrt[3]{x-6}+2}{x+2} = \lim_{x\to -2} \frac{\left(\sqrt[3]{x-6}+2\right)\left(\sqrt[3]{(x-6)^2}-\sqrt[3]{x-6}\cdot 2+4\right)}{(x+2)\left(\sqrt[3]{(x-6)^2}-\sqrt[3]{x-6}\cdot 2+4\right)} = </math>
<math> = \lim_{x\to -2} \frac{x-6+8}{(x+2)\left(\sqrt[3]{(x-6)^2}-\sqrt[3]{x-6}\cdot 2+4\right)} = </math>
<math> = \lim_{x\to -2} \frac{x+2}{(x+2)\left(\sqrt[3]{(x-6)^2}-\sqrt[3]{x-6}\cdot 2+4\right)} = </math>
<math> = \lim_{x\to -2} \frac{1}{\sqrt[3]{(x-6)^2}-\sqrt[3]{x-6}\cdot 2+4} = \frac{1}{\sqrt[3]{(-2-6)^2}-\sqrt[3]{-2-6}\cdot 2+4} = </math>
<math> = \frac{1}{\sqrt[3]{8^2}-\sqrt[3]{-8}\cdot 2+4} = \frac{1}{2^2+2\cdot 2+4} = \frac{1}{12} </math>